PERANAN TEKNOLOGI INFORMASI DALAM PENCEGAHAN VIRUS COVID-19 - Reza Rizki Pratama Suroso; Hesti Hasyim Hasyim (PTE FTK UIN Ar-Raniry, 2020)
This article aims to discuss about the importance of Information Technology in overcoming the Covid-19 virus. Information technology will continue to grow in line with the fast number of internet users. Based on the data obtained, it reaches that there are 175.4 million internet users in Indonesia. Based on the results of qualitative analysis, by direct observation, it can be concluded that the internet has become a medium that provides information to the public about the dangers and prevention efforts of COVID 19. However, the weaknesses of information technology included that the difficulty of filtering correct or wrong information. So, the users must sort and respond to any information from internet technology. The public needs to be aware of the covid-19 virus outbreak which has spread to hundreds of countries in the world, including Indonesia. Therefore, information technology should reach remote villages. With regard to the health aspect, information technology should reach out to the health center units and integrated with urban hospitals.